2004
DOI: 10.1007/s11130-004-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sensorial Properties (Color and Taste) of Amala, a Paste From Yam Chips Flour of West Africa, Through Flour Biochemical Properties

Abstract: Color and taste are permanent features of amala, a traditional thick paste obtained from yam chips flour. To assess these attributes, 23 yam chips presenting various quality attributes were processed. The sensory attributes of their derived amala were determined and some biochemical characteristics of yam flours measured. A panel defined five main taste attributes for amala: sweetness, bitterness, acidity, fermented, and roasted tastes. Amala color was measured instrumentally and sensory scores were highly cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…After centrifugation of the food suspension at 4140 rpm for 5 min, the supernatant was collected and filtrated through a 0.45 µm microporous membrane before the determination of organic acid contents (Mestres et al, 2004).…”
Section: Samples Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…After centrifugation of the food suspension at 4140 rpm for 5 min, the supernatant was collected and filtrated through a 0.45 µm microporous membrane before the determination of organic acid contents (Mestres et al, 2004).…”
Section: Samples Preparationmentioning
confidence: 99%
“…Injection volume was 20 µl and organic acids were detected at 210 nm. Citric, malic, lactic, formic, acetic, propionic acids were identified by retention and spectral data (Mestres et al, 2004).…”
Section: Chromatographic Conditionsmentioning
confidence: 99%
“…Total cyanide was determined, using the method described by Essers, Van der Grift, and Voragen (1996), modified by Padonou et al (2005). Soluble sugar content was determined by HPLC using an HPX87H column (Biorad, Hercules, USA) eluted with 5 mM sulphuric acid, using a refractometric detector (Mestres, Dorthe, Akissoe, & Hounhouigan, 2004). Sugar power (SP) was calculated according to Schaafsma (Schaafsma, 2008) as follows:…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…They reported that the yams from the kokoro group are more preferred by consumer than that of Florido. Also, other studies pointed out that yams tubers of kokoro group were mostly used for dried yam processing and its thick paste (amala) is generally the best preferred by consumers (Akissoé et al, 2001;Mestres et al, 2004). However, illegal substances such as fumigant type topstoxin and endosulfan (claimed by 33.3 and 29.3% of processors, respectively) are incorporated directly in cowpea grains and dried yams to control insects that attack during storage, while to ensure adequate dispersion, fumigants are often applied with airmoving equipment.…”
Section: Raw Materials and Ingredients Usedmentioning
confidence: 99%